2008
DOI: 10.1094/mpmi-21-12-1561
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Reactive Oxygen Species and Enhanced Stress Tolerance in Rubia cordifolia Cells Expressing the rolC Oncogene

Abstract: It is known that expression of the Agrobacterium rhizogenes rolC gene in transformed plant cells causes defense-like reactions, such as increased phytoalexin production and expression of pathogenesis-related proteins. In the present study, we examined whether this phenomenon is associated with increased production of reactive oxygen species (ROS). Single-cell assays based on confocal microscopy and fluorogenic dyes (2,7-dichlorofluorescein diacetate and dihydrorhodamine 123) showed reduced steady-state levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 56 publications
2
29
0
2
Order By: Relevance
“…The response of RolC plants was opposite in this case, showing decreased levels of fatty acids and hydroxyl fatty acids in CR samples compared to controls. Indeed, this result confirmed that the rol C gene expression prevents the production of ROS, as previously reported by Bulgakov et al [38] for Rubia cordifolia cells. GRCR plants showed no significant changes in lysolipid intensities or in fatty acid content.…”
Section: Chromium and Water Stressessupporting
confidence: 90%
“…The response of RolC plants was opposite in this case, showing decreased levels of fatty acids and hydroxyl fatty acids in CR samples compared to controls. Indeed, this result confirmed that the rol C gene expression prevents the production of ROS, as previously reported by Bulgakov et al [38] for Rubia cordifolia cells. GRCR plants showed no significant changes in lysolipid intensities or in fatty acid content.…”
Section: Chromium and Water Stressessupporting
confidence: 90%
“…The results indicated decreased intracellular ROS levels in rolC-expressing cells compared with control cells [11]. Moreover, the gene attenuated ROS accumulation after ROS-inducing treatments.…”
Section: Ros Homeostasis and Expression Of Antioxidant Genesmentioning
confidence: 89%
“…The first indication that the expression of individual rol genes in plant cells has an effect on the metabolism of reactive oxygen species (ROS) was published in 2008 [11]. This investigation was performed to determine whether the increased production of secondary metabolites in Rubia cordifolia cultured cells is associated with the oxidative burst.…”
Section: Ros Homeostasis and Expression Of Antioxidant Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Both genes, when expressed in plant cells, decreased intracellular ROS level. The rolB gene acts by inducing upregulation of antioxidant genes, thereby permanently supporting an active anti-oxidative status of transformed cells.…”
mentioning
confidence: 99%